Pelatihan Visual Thinking dan Dasar Desain Grafis Sejak Dini bagi Siswa MI Nurul Huda Kota Cimahi - Dini Rohmayani; Castaka Agus Sugianto; Akbar Maulana; Aris Haris Rismayana; Ayu Hendrati Rahayu (Yayasan Pemimpin Inovasi Science, 2026)
The development of graphic design in Indonesia is currently growing rapidly alongside the high industrial demand and educational interest. Introducing graphic design at an early age is crucial, as it can trigger children's creativity and interest through visual activities such as drawing. This study aims to introduce graphic design to elementary school students using Canva and Adobe Illustrator software. The method used is the delivery of material designed code-simplicity to be easily understood by children. Through this program, children are expected to understand the fundamentals of graphic design in an engaging and applicable manner.